POWER COMPONENTS ESTIMATION ACCORDING TO IEEE STANDARD 1459-2010 - Kušljević , Miodrag; Poljak, Predrag; Tomić, Josif (Journal on Processing and Energy in Agriculture, 2021)
In this paper, the design and implementation of a novel recursive method for the power measurement according to the IEEE Standard 1459–2010 have been described. The most important parts are adaptive band- and low-pass FIR filters that extract fundamental and dc components, respectively. In addition, by using oversampling techniques and decimation filters, coefficient sensitivity problems of the large-order FIR comb cascade structure are overridden and the parameter estimation accuracy is improved. The symmetrical components are estimated through transformation matrix of adaptive phase shifters. The effectiveness of the proposed techniques is demonstrated by simulation results.